Peran Music Director Terhadap Identitas Brand Radio Geronimo FM Yogyakarta - Guntur Eko Prasetyo (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2018)
Radio is one of the electronic media that has survived until now, although radio only produces entertainment in the form of sound but there are quite a lot of radio enthusiasts. There are quite a lot of radios operating in Indonesia, especially in Yogyakarta. In this case, one example is Geronimo FM radio, the radio has good credibility in the city of Yogyakarta. This article describes what the role of the Music Director on radio and how they work in shaping the brand identity. This study uses qualitative methods with a case study approach. The result is Music Director has the full right to determine the music that will air on the radio. Music Director also oversees the running of music played when the broadcast takes place so as not to get out of the provisions. Thus Music Director determines music, then radio brand identity is formed through songs that are played so as to form the perceptions of listeners in determining the identity of a radio